Exploring the EFL Students’ Reading Strategies Used on Reading Academic Articles - Giwang Indriyani; Indah Sekar Pertiwi (Institut Agama Islam Negeri Madura, 2021)
Reading activity is one of the essential skills for English language learners. Therefore, the use of reading strategies as one of the reading process rules should be considered. In considering the importance of reading strategies, this present study is intended to explore the reading strategies utilized by third-year EFL students on reading academic articles. To answer the research question, writers adopted the reading strategies questionnaire proposed by Oxford (1990). There were 21 statements and 31 samples involved in this present study. The significance of this study showed that meta-cognitive techniques were most frequently used by the students, followed by cognitive and affective, and then the less frequently used is social strategies. According to this finding, reading strategies should be noticed and taken as one of the considerations by lecturers and students to improve the EFL students’ comprehension of reading academic articles.